Navigating the Democratic Crisis: Indonesia’s Journey Through Political Ethics, Law, and Social Change - Artha Debora Silalahi; Rizal Mustansyir; Sindung Tjahyadi; Siti Murtiningsih (Universitas Katolik Parahyangan, 2024)
This article explores the crisis narrative surrounding the erosion of democracy in Indonesia, with a particular emphasis on political and ethical responsibilities. It examines the prevailing consensus on the consequences, factors, and conceptualization of democracy, especially concerning political trust and ethical governance. The discussion underscores how democracy evolves by deconstructing and reshaping societal structures, drawing on Kantian philosophy and the core pillars of democratic society. The paper highlights the inherent flaws in democratic principles, demonstrating how these imperfections permit varying degrees of freedom within societal practices. It advocates for the value of cultivating a culture of open, public discourse aboutcollective societal objectives. However, it also points out that the actual practice of lawmaking, implementation, and enforcement often deviates from its doctrinal ideals, particularly when the law’s purported impartiality contrasts with its impact on marginalized communities. These inconsistencies are examined as outcomes of the exercise of political power, illustrating that the law is shaped by political morality and legitimacy rather than being wholly independent. Furthermore, the article delves into the decline of democracy by engaging in dialogue about the process of its deterioration, rather than simply questioning the reasons behind it. This study also explores democracy and philosophy both in theory and practice, framing law as a reflective inquiry into the democratic process. Ultimately, it advocates for the political concepts of democracy to be subjected to scientific analysis and validation.